Effect of an obesogenic diet on the epigenetic profile of livers from Wistar rats and treatment with an aspalathin-rich rooibos extract - Abrahams, Yoonus (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.